Gain enhanced 5.8 GHz patch antenna with defected ground structure: design and measurement - Md. Nahid Hasan; Md. Sohel Rana (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
A rectangular microstrip patch antenna including a rectangular defective ground structure (DGS) is introduced to simultaneously enhance gain, bandwidth, and return loss while reducing antenna dimensions. This small antenna is engineered for 5.8 GHz applications, functioning throughout the frequency spectrum of 5.62 to 5.94 GHz. The design was executed on a 1.6 mm thick FR-4 substrate with a relative permittivity of 4.3, utilizing a microstrip line feed. The dimensions of the antenna are 31.75×28 ×1.6 mm³. The design approach utilized computer simulation technology (CST) Microwave Studio simulation software. The antenna attains resonance at 5.8 GHz, providing an initial bandwidth of 270 MHz and a return loss of -26 dB. A rectangular DGS was implemented to boost performance, yielding a 21.89% increase in bandwidth to 323 MHz and substantially enhancing the return loss from -23 dB to -47 dB. The gain increased from 3.95 dBi to 5.10 dBi, indicating a 30% enhancement, while sustaining an efficiency of around 83% at the resonant frequency. The antenna was constructed, and experimental measurements of parameters including gain and return loss closely matched the computer results.